2018
DOI: 10.1080/10942912.2015.1027921
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Antioxidant, and Lipid Peroxidation Inhibition of the Essential Oils ofLavandula OfficinalisL. in Iran

Abstract: The aim of present study was to evaluation the antioxidant potential of Lavandula officinalis on the basis of the chemical compositions of oils obtained by hydrodistillation. In the case of L.officinalis, thirteen compounds were identified representing the 96.53% of the total oil. The major constituents of the oil were described as α-pinene (20.14%), camphor (14.36%), menthol (32.51%) and 1,8-cineole (20.14%). The oils were also subjected to screening for their possible antioxidant activity by using 2,2-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The L. mairei EOs IC 50 value of reducing power ability was only twice a value of quercetin, exhibiting a high reducing power. The degree of antioxidant activity was variable in Lavandula genus; indeed the antioxidant capacity of L. mairei oils accords to what has been reported for other species of the Lavandula genus (Cherrat et al, 2014;Miri, 2015;Mohammedi and Atik, 2011). However, Miliauskasa et al (2004) detected weak antioxidant activity of EO obtained from L. angustiflolia.…”
Section: Antioxidant Activitysupporting
confidence: 81%
See 1 more Smart Citation
“…The L. mairei EOs IC 50 value of reducing power ability was only twice a value of quercetin, exhibiting a high reducing power. The degree of antioxidant activity was variable in Lavandula genus; indeed the antioxidant capacity of L. mairei oils accords to what has been reported for other species of the Lavandula genus (Cherrat et al, 2014;Miri, 2015;Mohammedi and Atik, 2011). However, Miliauskasa et al (2004) detected weak antioxidant activity of EO obtained from L. angustiflolia.…”
Section: Antioxidant Activitysupporting
confidence: 81%
“…Linalool and linalyl acetate, were determined as the two major compounds of essential oils of Lavandula angustifolia from Greece (Hassiotis et al, 2014). Chemical composition of essential oils from Lavandula officinalis from Iran shown that apinene, menthol and camphor were the main components (Miri, 2015). Ouedrhiri et al (2017) have reported that b-pinene, 1,8cineole and fenchone were the principal compounds of Lavandula dentata from north of Morocco.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Therefore, the presence of some aromatic substances in the EOs coupled to their particular chemical composition in hair formulations promotes physical, mental, and emotional balance, while adding pleasant odors to fiber and scalp. 28,46…”
Section: Oils Carriers Of the Eos And Formulationsmentioning
confidence: 99%
“…They are classified as terpene groups and can be found in large amounts in M. cajuputi leaves EO. Many previous studies reported that these compounds have a strong AC [18][19][20]. Essentially, there are no published studies on the AC of M. cajuputi leaves EO in the literature, it was not possible to compare our results.…”
Section: Determination Of the Chemical Compositions Of M Cajuputi Leaves Eo Gc-ms Analysis Was Usedmentioning
confidence: 74%